Thermoelectric effects in quantum dots - Yoshida, M. [UNESP]; Oliveira, L. N. (Elsevier, 2009)
We report a numerical renormalization-group study of the thermoelectric effect in the single-electron transistor (SET) and side-coupled geometries. As expected, the computed thermal conductance and thermopower curves show signatures of the Kondo effect and of Fano interference. The thermopower curves are also affected by particle-hole asymmetry. © 2009 Elsevier B.V. All rights reserved.
Keywords: Fano interference; Kondo effect; Numerical renormalization-group; Thermopower; Particle-hole asymmetry; Quantum Dot; Renormalization group; Single electron transistors; Thermal conductance; Thermoelectric effects; Thermopowers; Electric resistance; Magnetic materials; Semiconductor quantum dots; Thermoelectric power